Anatomical variations of maxillary sinus septa and their relationship to the antral volume in patients with different skeletal profiles / Noor Azwani Mat Nawi - Noor Azwani , Mat Nawi (2018)
Maxillary sinus pneumatization may result in the formation of bony ridges (septa) and an increase in antral volume. This CBCT study was conducted to determine the prevalence, height, location, and variations of maxillary sinus septa, at the same time determining their relationship to the antral volume in patients with different skeletal profiles. Methods: Two hundred four septa in 137 maxillary sinus segments from 150 patients with different skeletal profiles were studied. Bony projections with a minimum height of 2.5mm were considered as septa. Volumetric analysis of the maxillary sinus was conducted using MIMICS 16.0 software. Results: The mean age of the subjects was 41.13 (SD 17.23) years; this includes 48% male and 52% female from three major ethnics. The prevalence of sinus septa was 45.7%. Three quarters of septa (75.9%) was observed in bilateral antrum. Most septa were located in the mid-antral floor (66.7%). There were variations in mean septal height and location depending on the plane of examination. The average volume of maxillary sinus segment was 16.36 (SD 0.50) cm3 in Class I, 17.96 (SD 0.59) cm3 in Class II and 16.65 (SD 0.55) cm3 in Class III patients, unaffected by the side, and patientsï¿½ gender and ethnicity. Males manifested larger antral volume than female. The skeletal profile did not influence the prevalence of maxillary sinus septa and antral volume. Conclusion: This study has provided detailed information of maxillary sinus septa and antral volume, both of which are not significantly affected by the differences in patientsï¿½ skeletal profile. Keywords: cone-beam computed tomography; maxillary sinus septa; antral volume; skeletal profile.